2018
DOI: 10.1364/oe.26.000531
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal expansion coefficient of carbon fiber reinforced composites using electronic speckle interferometry

Abstract: An optical system for measuring the coefficient of thermal expansion (CTE) of materials has been developed based on electronic speckle interferometry. In this system, the temperature can be varied from -60°C to 180°C with a Peltier device. A specific specimen geometry and an optical arrangement based on the Michelson interferometer are proposed to measure the deformation along two orthogonal axes due to temperature changes. The advantages of the system include its high sensitivity and stability over the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…Figure 10 showed that the value of CTE varied with increasing temperature. This was consistent with results from previous studies [4,8,29,30]. Sample 2 had the highest range of CTE compared to sample 1 and 3.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Figure 10 showed that the value of CTE varied with increasing temperature. This was consistent with results from previous studies [4,8,29,30]. Sample 2 had the highest range of CTE compared to sample 1 and 3.…”
Section: Resultssupporting
confidence: 93%
“…Sample 1 refers to the sample without a protective coating; sample 2 refers to the sample with AO protective coating, and sample 3 refers to the sample with UV protective coating. The CTE showed a non-linear temperature dependence, which was consistent with results from previous studies [4,8,29,30]. Each data point represents the median CTE value calculated based on a range of temperature and strain measurement during a mission operation session.…”
Section: Cte Measurementsupporting
confidence: 89%
“…While manufacturing the samples with embedded strain gauges, the alignment of the gauges with respect to the direction of the carbon fibers was also shown to modify the readings of the applied strain. The preliminary results from the MM appear to match the previous tests [31]. To have a complete understanding of the material degradation, a correlation of the orbital data with the ground calibration information will be performed.…”
Section: Materials Mission (Mm)mentioning
confidence: 58%
“…The pole s 1 is over the origin (of the complex s-plane), and it was generated by the direct component of our interference pattern. 9 Interference Pattern Representation on the Complex s-Plane DOI: http://dx.doi.org /10.5772/intechopen.89491 To generate the Bode diagram, we consider the next complex function…”
Section: âãmentioning
confidence: 99%
“…Many coherence interferometers systems find practical applications for the physical parameter measurement, such as are temperature, strain, humidity, pressure, level, current, voltage, and vibration [1][2][3][4][5][6][7][8][9][10]. Physical implementation and signal demodulation are very important for the good measurement.…”
Section: Introductionmentioning
confidence: 99%